South African experience consolidating person-level health data for both service and research in a single environment - Boulle, Andrew; Heekes, Alexa; Mutemaringa, Themba; Smit, Mariette; Foster, Rosemary; Tiffin, Nicki (International Journal of Population Data Science, 2020)
Introduction There are few examples of functional health information exchange environments or data linkage centres in the African settings. New opportunities are emerging as unique health identifiers and patient registration systems are being established nationally in many countries, and increasingly individuated health data are available for linkage, often linked to priority global health initiatives such as to support HIV and tuberculosis services. Objectives and Approach We sought to establish a province-wide health information exchange and data centre for individuated health data, leveraging a unique identifier and available individuated data. The intention with the Provincial Health Data Centre (PHDC) was to create a single well-governed environment which could simultaneous fulfil the functions of an exchange directly supporting care, as well as support research requests. Often the demands of academics, funders and global agencies for reporting result in data consolidation for research and reporting taking precedence over service delivery. Results Through pragmatic use of data from all sources, the PHDC is able to usefully enumerate many health conditions of interest with sufficient fidelity for both service and research purposes. For research data requests, there has been a huge improvement in data governance alongside increased data availability as a result of the single environment with clear procedures for patient protection, and the benefits of data linkage prior to anonymisation. Many of the inference approaches have benefited hugely from interactions with researchers, which has in turn improved the quality of outputs for routine care. Conclusion / Implications In maturing digital health environments which are establishing consolidated data environments for the first time, aspiring from the start to a single well-governed environment for both patient care and research, is a virtuous model with many benefits over fragmented data linkage efforts